المسرح السياسي عند يحي موسى مسرحية تحت سقف الشيطان نموذجا - خليل, كركوبي, يمينة نعيمة; إحميمة, صفاء (University of El-oued, 2022)
الجمالية – التلقي – النكتة – الشعبية –السوفية.الخسائر، وبقبول واضح من دول المنطقة وشعوبها، وهذا ما حصل ليكون من بين أهم نتائج الحرب في جانب الحلفاء، ويقابله خسائر عديدة لعرب الخليج من اقتصادهم و أمنهم واستقرارهم الاجتماعي، وكذلك خسائر العراق السياسية والاجتماعية والاقتصادية كبيرة واستراتيجية سوف لن يقوى على استمرار تحملها في المدى البعيد. لقد كشفت مسرحية " تحت سقف الشيطان " عن امتلاك الكاتب لرؤية درامية ورسالة فكرية نود إيصالها من خلال معالجة قضايا اجتماعية وسياسية لعصر مليء بالتناقضات من خلال تقديمه للنماذج السلبية للمجتمع مما تسبب له في منعه من إكمال نشرها. ancient times, political theater has not been separated from society by its various issues, and has always been a means of expressing them and a space for defining the ideas and ideologies of societies. The writer Yahya Musa portrays us through his play under (the roof of the devil) the second Gulf War, in which several factors were combined in its occurrence at the international, regional and local levels, Iraq was in the light of the hierarchical military composition implemented, and the president (Saddam Hussein) personality other than his government together is the main party in its occurrence, as they paved by inflaming a crisis with Kuwait, and their resort to the use of force to deal with it to an American intervention under the umbrella of the United Nations, as long as offset by numerous losses For the Gulf Arabs of their economy, security and social stability, as well as Iraq's political, social and economic losses are significant and Strategic will not be able to sustain them in the long term. "Under the roof of the devil" revealed that the writer had a dramatic vision and an intellectual message that we would like to convey by addressing the social and political issues of an era full of contradictions by presenting the negative models of society, which caused him to prevent him from completing its publication.
Keywords: المسرح السياسي - يحيى موسى - تحت سقف الشيطان; Political theater - Yahya Musa - Under the roof of Satan